A RARE CASE OF PERITONEAL METASTASIS FROM FOLLICULAR THYROID CARCINOMA WITHOUT PRIMARY LESION IN A PATIENT WITH HYPOPITUITARISM - Porntharukchareon, Thachanun; Mahasandanaa, Thanaporn; Samdaengpan, Chayanee; Sricharunrat, Thaniya; Kunawudhi, Anchisa (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 44-year-old female presented with multiple peritoneal nodules. Despite negative CT scans of the chest, abdomen, and gynecologic examination, a peritoneal biopsy confirmed metastatic tumor cells displaying thyroid follicular cell characteristics, supported by positive CK-7, thyroglobulin, and TTF-1 markers. A thyroid ultrasound detected a small left thyroid nodule, expected to have no impact on the thyroid function test. However, it revealed low FT4 and normal TSH levels, suggesting secondary hypothyroidism. A pituitary MRI revealed a reduced pituitary gland height and a 0.4 cm less enhancing nodule in the right anterior lobe. The patient underwent total thyroidectomy, however, no evidence of follicular thyroid carcinoma was observed. After radioactive iodine (RAI) treatment, a whole body scan revealed thyroid remnants and multiple peritoneal nodules with radioiodine uptake in the follow-up scan. Non-stimulated thyroglobulin levels at 3 and 6 months after RAI were 1798 and 1182 ng/mL, respectively, prompting the decision for a second RAI therapy.